Research on Flaw Detection Experiment of Ultrason. Issue 1 (1st June 2022) - Zhong, Haotian; Zhang, Li; Shi, Yipeng; Xia, Zhenbiao; Duan, Jingwen; Shi, Bowen; Shi, Huiyun; Li, Yanjun
Abstract: With the progress of modern science and technology, people have developed a special equipment to detect whether there is damage inside metal and non-metallic materials.Ultrasonic nondestructive testing detector is a portable industrial nondestructive testing detector, which cannot damage the detection object under the premise of the internal structure of the comprehensive detection object, but easily forms blind spots in the area of 2-3mm on the material surface and the nearby surface.Ultrasonic phased array nondestructive testing detector can compensate for this disadvantage and have high detection flexibility.This paper analyzes the advantages and disadvantages of the ultrasonic flaw detector and the ultrasonic phased array flaw detector.